2021
DOI: 10.1177/02673231211012141
|View full text |Cite
|
Sign up to set email alerts
|

Selective exposure in different political information environments – How media fragmentation and polarization shape congruent news use

Abstract: Previous research posits that individual predispositions play an essential role in explaining patterns of selective exposure to political information. Yet the contextual factors in the political information environment have received far less attention. Using a cross-national and quasi-experimental design, this article is one of the first to investigate how political information environments shape selective exposure. We rely on a unique two-wave online survey quasi-experiment in five countries (Switzerland, Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 73 publications
(111 reference statements)
0
17
0
2
Order By: Relevance
“…Fletcher and Nielsen (2017) found the UK to have a more fragmented audience than Denmark, Germa ny, France, Spain, and the US, and Denmark to have a more fragmented audience than Spain and the US. In countries with a higher degree of fragmentation, a higher selective exposure is found (Steppat et al, 2022).…”
Section: Audience Fragmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Fletcher and Nielsen (2017) found the UK to have a more fragmented audience than Denmark, Germa ny, France, Spain, and the US, and Denmark to have a more fragmented audience than Spain and the US. In countries with a higher degree of fragmentation, a higher selective exposure is found (Steppat et al, 2022).…”
Section: Audience Fragmentationmentioning
confidence: 99%
“…Another question is whether the development of high-choice media en vironments leads to a fragmentation of media users. Here, little overall fragmentation of recipients is shown for offline and online media, and therefore, it is not possible to speak of audience fragmentation (or echo chambers) (Fletcher & Nielsen, 2017;Steppat et al, 2022). However, there are, again, differences between media systems.…”
Section: Audience Fragmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Este fenómeno debe relacionarse con el denominado "sesgo de selección", según el cual los ciudadanos tienden a elegir medios y noticias que confirman sus opiniones o preferencias previas (Barnidge et al, 2020;Ling, 2020). A esa misma conducta apunta la teoría de la "exposición selectiva" (Steppat et al, 2021;Stroud, 2017). Además, los prejuicios introducen sesgos en la selección y redacción de noticias, en ocasiones de manera involuntaria o inconsciente (Hackett, 1984).…”
Section: Periodismo Y Prejuiciosunclassified
“…Other studies focused on the role of users’ ability to acquire information from diverse channels in silencing rumors (Chua and Banerjee, 2017; Mason et al, 2011). Furthermore, Steppat, Castro, and Esser (2021) found that users from countries with more inclusive political information environments are the least likely to engage in selective exposure in their daily news use. They also found that selective exposure is slightly more frequent among regular social media users than other media.…”
Section: Introductionmentioning
confidence: 99%